Predicting the Outcome of First Episode Psychosis Subjects by Assessing Dorsolateral Prefrontal Cortex Volume - Arathil, Praveen; Bansal, Rahul; Kuruppath, Arun (Archives of Psychiatry Research, 2024)
Aim: Dorsolateral prefrontal cortex (DLPFC), Neurological Soft Signs (NSS) and Cognitive impairment have been described as predictors of outcome of First Episode Psychosis (FEP), therefore we aimed to find the predictors of clinical, social and functional outcome variables in a cohort of first episode non affective psychotic subjects. Subjects and Methods: A prospective follow up study was conducted from August 2018 to August 2020 in a tertiary care hospital of South India. A semi-structured questionnaire was given to all subjects for socio-demographic details. All subjects were assessed with Heidelberg scale, Bender Gestalt Test (BGT) and underwent MRI Brain 3D volumetric scan to examine NSS, cognitive impairment, and DLPFC volume at baseline respectively. Brief Psychiatric Rating Scale (BPRS) and Social and Occupational Functioning Assessment Scale scales (SOFAS) were administered at baseline, 1 month and at three month follow up. At 3 months, clinical and socio-functional outcome was defined by BPRS scores and SOFAS scores. Pearson’s correlation was found between DLPFC volume of all subjects, BPRS, BGT scores at baseline with BPRS and SOFAS at 3 months. To test the statistical significance of the comparison of mean values of all continuous clinical and demographic parameters between two groups of BPRS and SOFAS, Mann Whitney U test was used. Results: Smaller DLPFC volume predicted clinical, socio-functional outcome significantly. A significant moderate correlation was found between NSS and BPRS scores at baseline. Conclusion: Baseline right DLPFC volume can be an important predictor of clinical and socio-functional outcome in FEP.